Saibai Island minaral : traditional and contemporary patterns and designs - Kabai, Belinda (Thuringowa, Qld. : Black Ink Press, 2004)
Showcases the work of nine artists from Saibai; the women produced the work in art classes over a period of twelve months; the men's work includes drums, carvings and headdresses.
Keywords: Torres Strait Islanders -- Queensland -- Saibai Island -- Art; Art -- Queensland -- Saibai Island; Women artists -- Queensland -- Saibai Island; Art - Exhibitions; Art - Artists - Women; Art - Artists - Men; Saibai Island (Qld TSI SC54-08)